Unprecedented overlap of Tourette syndrome and drug-resistant epilepsy in a young patient with Bardet–Biedl syndrome: A case report - Eliane Batista Silva; Cezar Filho dos Santos Liberal; Gabriella Cláudia Figueiredo Melo; Arthur Severiano Dos Santos Pontes; Randerson José De Araujo Sousa; Marcos Manoel Honorato (Acta Neurológica Colombiana, 2026)
Introduction: Drug-resistant epilepsy affects approximately 25% of patients with epilepsy and requires complex, multidisciplinary therapeutic approaches. When associated with neuropsychiatric comorbidities and rare genetic syndromes, such as Bardet–Biedl syndrome (BBS), a primary ciliopathy, diagnostic and therapeutic challenges are further intensified. Case presentation: A Brazilian male patient with neuropsychomotor developmental delay, hereditary retinopathy, and motor and vocal tics since childhood was evaluated at 10 years of age due to involuntary movements, vocalizations, and behavioral disturbances. He was diagnosed with autism spectrum disorder (ASD), mild intellectual disability, and Tourette syndrome (TS), accompanied by intermittent psychotic symptoms. At 16 years of age, he developed a complex epilepsy phenotype characterized by focal seizures associated with visual hallucinations, progressing to bilateral tonic– clonic seizures. Recurrent episodes of functional/dissociative seizures were also observed. The patient subsequently underwent whole-exome sequencing, which led to the diagnosis of BBS type 1, accounting for the multisystem involvement and the clinical complexity of the case. Discussion: This case expands the clinical spectrum of BBS by documenting the coexistence of its classical manifestations with TS, ASD, refractory epilepsy, and functional dissociative seizures. Although ASD is increasingly recognized as a neurodevelopmental comorbidity in ciliopathies, persistent tic disorders remain rarely reported, suggesting that ciliary dysfunction may contribute to susceptibility to complex neurodevelopmental phenotypes. Conclusion: This case illustrates a rare and previously undescribed overlap between clinical findings consistent with TS and a complex epileptic phenotype. Furthermore, in the context of initial diagnostic uncertainty, genetic sequencing was essential to confirm the diagnosis of BBS.